Practical implementation of robust MR-thermometry during clinical MR-guided microwave ablations in the liver at 1.5 T. (November 2019) - Gorny, K.R.; Favazza, C.P.; Lu, A.; Felmlee, J.P.; Hangiandreou, N.J.; Browne, J.E.; Stenzel, W.S.; Muggli, J.L.; Anderson, A.G.; Thompson, S.M.; Woodrum, D.A.
Highlights: Practical measures to achieve robust real-time MR thermometry during clinical hepatic microwave ablations are described. Quality Assurance protocol was developed ensuring consistent high quality imaging during MR-guided microwave procedures. Imaging protocol was modified to account for respiratory movement and reduce respiratory motion artifact. These measures consistently reduced image noise and artifacts improving safety and effectiveness of microwave treatments. Abstract: Practical non-invasive equipment modifications and effective acquisition methods to achieve robust and reliable real-time MR thermometry for monitoring of clinical hepatic microwave ablations were implemented. These included selection of the microwave generator location (inside versus outside the MR scan room), the number of radiofrequency chokes added to the microwave generator's coaxial lines, and the use of copper wool to maximize their electrical grounding. Signal-to-noise ratio (SNR) of MR thermometry images of a small fluid-filled phantom acquired during activation of microwave antenna were used to evaluate image quality as a function of each modification. SNR measurements corresponding to both locations of the microwave generator were comparable and so it was located outside the MR scan room. For this location, addition of one RF choke on the power and four chokes on the sensor coaxial lines was found to be optimal, corresponding to a 68% increase in SNR. Furthermore, image quality strongly depended on the proper electrical grounding of the power and sensor lines. SNR ratio (relative to SNR of baseline images) during activation of microwave generator was found to be 0.49 ± 0.28 without adequate grounding, and 0.88 ± 0.08 with adequate grounding (p = 0.002, Student's t -test). These SNR measurements were sufficiently sensitive to detect issues related to equipment performance and hence formed part of the quality assurance testing performed prior to each clinical treatment. Incorporating these non-invasive approaches resulted in significant improvements to image quality and, importantly while maintaining the clinical integrity of the microwave system which is of paramount importance in a highly regulated healthcare environment.